Research on the Effects of Biochar Addition on Soil Carbon Emissions: CO2 and CH4 - Zhai, Liping (International Journal of Natural Resources and Environmental Studies, 2026)
Soil carbon emissions significantly influence the global carbon balance as a major component of the terrestrial carbon pool. Biochar, an emerging soil amendment, has garnered significant interest for its potential to enhance carbon sequestration, improve soil fertility, and mitigate greenhouse gas emissions. However, the impacts of biochar on soil CO2 and CH4 emissions are complex and context-dependent, varying with biochar properties, soil types, and environmental conditions. Integrating proposed mechanisms for biochar-induced soil greenhouse gas mitigation with statistical analyses of published literature, this review systematically examines the effects of biochar on CO2 and CH4 emissions and identifies future research priorities. Specific focus is given to biochar produced at pyrolysis temperatures of 500-600 °C, its application in flooded soils, and its effects within straw-return agricultural systems. Through critical analysis of existing literature, this review aims to offer insights to guide further research and practical applications in this field.